IDO1 Expression in Ovarian Cancer Induces PD-1 in T Cells via Aryl Hydrocarbon Receptor Activation - Amobi-McCloud, Adaobi; Muthuswamy, Ravikumar; Battaglia, Sebastiano; Yu, Han; Liu, Tao; Wang, Jianmin; Putluri, Vasanta; Singh, Prashant K.; Qian, Feng; Huang, Ruea-Yea; Putluri, Nagireddy; Tsuji, Takemasa; et al. (Frontiers in Immunology, 2021)
The immunoregulatory enzyme, indoleamine 2,3-dioxygenase (IDO1), and the PD-1/PDL1 axis are potent mechanisms that impede effective anti-tumor immunity in ovarian cancer. However, whether the IDO pathway regulates PD-1 expression in T cells is currently unknown. Here we show that tumoral IDO1 expression led to profound changes in tryptophan, nicotinate/nicotinamide, and purine metabolic pathways in the ovarian tumor microenvironment, and to an increased frequency of PD-1+CD8+ tumor-infiltrating T cells. We determined that activation of the aryl hydrocarbon receptor (AHR) by kynurenine induced PD1 expression and this effect was significantly abrogated by the AHR antagonist CH223191. Mechanistically, kynurenine alters chromatin accessibility in regulatory regions of T cell inhibitory receptors, allowing AHR to bind to consensus XRE motifs in the promoter region of PD-1. These results enable the design of strategies to target the IDO1 and AHR pathways for enhancing anti-tumor immunity in ovarian cancer.